2017
DOI: 10.1007/s00221-017-5096-z
|View full text |Cite
|
Sign up to set email alerts
|

How effector-specific is the effect of sequence learning by motor execution and motor imagery?

Abstract: The aim of the present study was twofold. First, we wanted to examine how effector specific the effect of sequence learning by motor execution is, and second, we wanted to compare this effect with learning by motor imagery. We employed a Go/NoGo discrete sequence production task in which in each trial a spatial sequence of five stimuli was presented. After a Go signal the corresponding spatial response sequence had to be executed, while after a NoGo signal, the response sequence had to be mentally imagined. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
3
0
5
Order By: Relevance
“…Behavioral research with this DSP task resulted in various cognitive models (Abrahamse et al 2013 ; Verwey 2001 ; Verwey et al 2015 ). In addition, a variety of DSP studies have explored the neural substrate of motor sequence learning using EEG (e.g., De Kleine and Van der Lubbe 2011 ; Sobierajewicz et al 2017 ), fMRI (Jouen et al 2013 ; Verwey et al 2019 ), and also TMS (Ruitenberg et al 2014 ; Verwey et al 2002 ). Those studies confirmed that the SMA is involved in executing practiced DSP sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral research with this DSP task resulted in various cognitive models (Abrahamse et al 2013 ; Verwey 2001 ; Verwey et al 2015 ). In addition, a variety of DSP studies have explored the neural substrate of motor sequence learning using EEG (e.g., De Kleine and Van der Lubbe 2011 ; Sobierajewicz et al 2017 ), fMRI (Jouen et al 2013 ; Verwey et al 2019 ), and also TMS (Ruitenberg et al 2014 ; Verwey et al 2002 ). Those studies confirmed that the SMA is involved in executing practiced DSP sequences.…”
Section: Introductionmentioning
confidence: 99%
“…As musicians have to train fine motor skills significantly more often than novices, learning related motor skills may be easier for musicians than for non-musicians. The learning of a motor skill is thought to involve both a motor and a more cognitive level [ 2 , 3 , 4 ], and recent research suggests that motor imagery may only be related to a cognitive level [ 5 ]. The potential benefit for musicians may thus be related to this cognitive and/or motor level, and one might propose that musicians additionally benefit from motor imagery.…”
Section: Introductionmentioning
confidence: 99%
“…The latter results suggest that relevant motor areas are activated during both motor execution and motor imagery, which corroborates with several earlier findings [ 8 , 9 ]. In another study, it was examined whether learning effects of motor execution and motor imagery were muscle-specific or not [ 5 ]. This was done by varying the execution mode as sequences were either learned with four fingers or only with the index fingers of both hands.…”
Section: Introductionmentioning
confidence: 99%
“…A imagética induz o aprendizado motor, conforme estudos sobre a reabilitação de pacientes com déficits motores, cognitivos ou intelectuais e aquisição ou aperfeiçoamento de habilidades esportivas, artísticas ou cirúrgicas 193,204,[205][206][207][208][209][210][211][212] . Contudo, o treinamento real é superior à imagética, que é superior à ausência de treino 204,205,212,213 .…”
Section: Caracterização Da Dmfunclassified
“…Embora a capacidade de praticar imagética seja preservada nas pessoas amputadas, a literatura revela que a impossibilidade do movimento real e concreto pela ausência do membro, diminui a capacidade de imaginar, tornadoa mais difícil ou mesmo impossível 212,[231][232][233] com menor precisão do controle do movimento imaginário, à semelhança de pessoas com membros imobilizados, mesmo que por período temporário 204,206,209 .…”
Section: Caracterização Da Dmfunclassified